Phylogenetic and functional characterization of water bears (Tardigrada) tubulins - Novotná Floriančičová, Kamila; Baltzis, Athanasios; Smejkal, Jiří; Czerneková, Michaela; Kaczmarek, Łukasz; Malý, Jan; Notredame, Cedric; Vinopal, Stanislav (Scientific reports, 2023)
Tardigrades are microscopic ecdysozoans that can withstand extreme environmental conditions. Several tardigrade species undergo reversible morphological transformations and enter into cryptobiosis, which helps them to survive periods of unfavorable environmental conditions. However, the underlying molecular mechanisms of cryptobiosis are mostly unknown. Tubulins are evolutionarily conserved components of the microtubule cytoskeleton that are crucial in many cellular processes. We hypothesize that microtubules are necessary for the morphological changes associated with successful cryptobiosis. The molecular composition of the microtubule cytoskeleton in tardigrades is unknown. Therefore, we analyzed and characterized tardigrade tubulins and identified 79 tardigrade tubulin sequences in eight taxa. We found three α-, seven β-, one γ-, and one ε-tubulin isoform. To verify in silico identified tardigrade tubulins, we also isolated and sequenced nine out of ten predicted Hypsibius exemplaris tubulins. All tardigrade tubulins were localized as expected when overexpressed in mammalian cultured cells: to the microtubules or to the centrosomes. The presence of a functional ε-tubulin, clearly localized to centrioles, is attractive from a phylogenetic point of view. Although the phylogenetically close Nematoda lost their δ- and ε-tubulins, some groups of Arthropoda still possess them. Thus, our data support the current placement of tardigrades into the Panarthropoda clade.
Keywords: Tardigrada; Tubulin; Animals; Phylogeny; tubulin; zvířata; fylogeneze